2011
DOI: 10.1021/ma102515c
|View full text |Cite
|
Sign up to set email alerts
|

Terpolymerization of Linear and Alicyclic α-Olefins with Norbornene and Ethylene by ansa-Metallocene Catalysts

Abstract: Ethylene−norbornene (E−N) terpolymerization experiments using the linear olefin 1-octene (O) or the alicyclic vinylcyclohexane (VCH) were conducted with two different ansa-metallocene compounds Zr(η5:η5-C5H4CPh2C13H8)Cl2] (1) and [Zr{(η5-2,5-Me2C5H2)2CHMe}Cl2] (2). The terpolymers obtained were investigated in detail by determining microstructure and termonomer contents by 13C NMR, molar masses, and thermal properties. Chain end group analysis gave insight into factors that influence termonomer insertion and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Such copolymers are called as cyclic olefin copolymers (COCs). The development of single‐site catalysts has realized the copolymerization not only with ethylene but also with α‐olefins, styrene, and olefins with functional groups …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such copolymers are called as cyclic olefin copolymers (COCs). The development of single‐site catalysts has realized the copolymerization not only with ethylene but also with α‐olefins, styrene, and olefins with functional groups …”
Section: Introductionmentioning
confidence: 99%
“…The addition of third comonomer is the efficient way to introduce unreactive comonomer. Synthesis of some cyclic olefin terpolymers are recently investigated . The aim of this work is to synthesize the NB‐enriched NB‐IP copolymer using fluorenylamido‐ligated titanium catalyst 1 , which showed very high activity for the (co‐)polymerizations of NB with α‐olefins and dicyclopentadiene with ethylene .…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity of incorporating other olefins (as a third monomer) into the poly(ethylene- co -norbornene) backbone may lead to improvements in the mechanical or other physical properties of the polymer. There are only a few reports on terpolymerization of ethylene and norbornene [ 28 , 29 , 30 , 31 ]. The introduction of a termonomer, either a linear α-olefin, such as 1-octene (O), or an alicyclic α-olefin, like vinylcyclohexane, has been reported by Marconi et al [ 29 ], but a strong decrease of M w has been observed for both 1-octene and vinylcyclohexane.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports on terpolymerization of ethylene and norbornene [ 28 , 29 , 30 , 31 ]. The introduction of a termonomer, either a linear α-olefin, such as 1-octene (O), or an alicyclic α-olefin, like vinylcyclohexane, has been reported by Marconi et al [ 29 ], but a strong decrease of M w has been observed for both 1-octene and vinylcyclohexane. It was shown that 1-octene and vinylcyclohexane behave as chain termination/transfer agents, that is they act as reagents that both terminate and facilitate the reinitiation of a growing polymer chain [ 29 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on polymerization using a metallocene catalysts began with the identification of the structure of ferrocene by Wilkins and Fischer in 1952 and was developed further by Kaminsky in the 1980s 1,2 . In the case of copolymerization using a metallocene catalyst, preparing polymers with a narrow molecular weight distribution, high stereo-regularity and uniform comonomer incorporation is much easier than when a conventional Ziegler-Natta catalyst is used.…”
Section: Introductionmentioning
confidence: 99%